"Research-Based Learning" Workshop for English Teachers: Strategies for Improving Scientific Writing Skills and Their Application in Research-Based Learning Projects - Nugraha, Irsyad; Julianna, Ainna; Alawiyah, Sopi; Hidayat, Perdi; Ramadhan, Mochamad Randi; Sholihah, Kiah Nur; Sidiq, Muhammad Japar; Nuralifah, Rini; Fatimah, Siti; Nursabani, Riyandi Febriana; Samsudin, Taupik; Alami, Intan; Ismiati, Iis (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service program aimed at enhancing English teachers' capability in the Garut Regency by introducing Research-Based Learning (RBL) as a method to improve scientific writing skills among students. The workshop, held on June 17-18, 2024, provided teachers with theoretical foundations and practical techniques for implementing RBL, emphasizing the importance of integrating research into the learning process. The first day focused on conceptual understanding of RBL and academic writing, while the second day shifted to hands-on training where teachers designed research-based learning projects. Results from pre-test and post-test evaluations showed a significant improvement in teachers' understanding, with an average increase of 30%. This initiative is expected to enhance the teaching of scientific writing and critical thinking among students in Garut.